Cartographie des risques d’érosion hydrique des sols au moyen du Système d’Information Géographique Cas du bassin versant de l’oued Fergoug - KOUDDED Mohamed (My University, 2013)
ntegration of maps of the Universal soil loss equation factors into GIS, which can be used to estimate risks of soil erosion, in a fast and efficient way, to disentangle complexity and interdependence of factors in erosion risks analysis and to better determine the impact of each factor and to evaluate its contribution to soil loss. Integration of GIS and the application of the USLE formulas, by producing a synthetic map of sensitivity degrees to erosion, to establish the decisive factors which controls erosion which are by order of importance, the climate factors , the slope, the soil erodibility , the vegetable cover and practical culturally .
Keywords: Water erosion, watershed, risk mapping, Geographical Information System, Universal Soil Loss Equation